Synthesis and characterization of biocompatible hybrid coating on WE54 Mg alloy for implant applications - Hazera Khatun; Mostafizur Rahman; Saifullah Mahmud; Mosiur Rahaman; Osman Ali; Yusuf Ali; Sadia Islam (Results in Engineering, 2024)
Magnesium (Mg) and its alloys are prospective biodegradable metallic implant materials. This research focuses on addressing the high corrosion rate of Magnesium (Mg) and WE54 Mg alloys, limiting their biomedical applications as biodegradable metallic implants. The study proposes a novel approach by developing hybrid coatings on these materials, combining organic PLA (poly-lactic acid) and inorganic HA (hydroxyapatite) substances. The hybrid coatings exhibit significantly improved corrosion protection and biocompatibility, reducing degradation and in vitro corrosion rates in body fluid solutions. Immersion testing indicates a substantial decrease in the degradation rate in simulated body fluid (SBF). Electrochemical studies reveal that the HA/PLA coating enhances corrosion resistance by about 280 times compared to unmodified Mg and approximately 230 times compared to uncoated WE54 Mg alloy. Cytotoxicity tests affirm improved bioactivity and biocompatibility, suggesting the potential of HA/PLA hybrid coatings as promising solutions for fabricating biodegradable implants in biomedical applications.